أثر الصورة الذهنية والدليل المادي على زيادة رضا عملاء المنظمات الخدمية (دراسة استقصائية على المستشفيات الخاصة) - مرهج منذر; الهايس خالد (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الاقتصادية والقانونية, 2018)
هدفت هذه الدراسة إلى استكشاف العلاقة ذات الصلة بالدور الذي تؤديه الصورة الذهنية والدليل المادي, ورضا المستفيدين من الخدمة الصحية خلال الأزمة التي تمر بها البلاد وفي مرحلة إعادة الإعمار, وكذلك استطلاع الإمكانية الفعلية للاستفادة من الصورة الذهنية والدليل المادي في المستشفيات الخاصة في كل من محافظتي دمشق واللاذقية بشكل خاص وباقي المستشفيات الخاصة في الجمهورية العربية السورية بشكل عام. ومن أجل تحقيق أهداف الدراسة واختبار فرضياتها , فقد تم تطوير استبيان خاص بجمع البيانات من عينة الدراسة التي بلغ عدد أفرادها (600) مقدم للخدمة و (300) مستفيد من الخدمة, موزعين على (10) مستشفيات في دمشق و (5) مستشفيات في اللاذقية, بالإضافة إلى العيادات الخاصة, وقد بلغ عدد الاستبيانات الخاضعة للتحليل (564) استبيان, شكلت ما نسبته (94%) من إجمالي مقدمي الخدمة, و(271) استبيان , شكلت ما نسبته (90.3%) من إجمالي استبيان المستفيد من الخدمة الصحية . وباستخدام مقاييس الاختبارات الإحصائية في النظام الإحصائي (SPSS 20) توصلت الدراسة إلى عدة نتائج أهمها الأتي: 1) إن الصورة الذهنية والدليل المادي تؤثر تأثيراً طردياً معنوياً بزيادة رضا المستفيدين من الخدمة الصحية بنسبة (58.6%) من وجهة نظر المستفيدين من الخدمة الصحية. 2) إن الصورة الذهنية والدليل المادي تؤثر تأثيراً طردياً معنوياً بزيادة رضا المستفيدين من الخدمة الصحية بنسبة (52.3%) من وجهة نظر مقدمي الخدمة الصحية. وختاماً: فقد خلصت الدراسة إلى مجموعة من التوصيات التي جرى استخلاصها في ضوء النتائج التي توصلت إليها الدراسة. This study has aimed to explore the relationship between the mentality image and materialistic pilot and customer satisfaction , as well as explore the real possibility for the application of these and benefiting from it, on private hospitals in each of the province of Damascus and lattakia, in particular and the rest of the private hospitals in the Syrian Arab Republic in general. In order to achieve the objectives of the study and testing of hypotheses, has been developed a special questionnaire to collect data from a sample of the study that the number of members (600), submitted by the Service and (300) beneficiaries of the service, Distributors (10) Hospitals in Damascus, and (5) hospitals in lattakia, as well as private clinics, the number of questionnaires have been subject to analysis (564) questionnaire. Representing (94%) of the total service providers, and (271) questionnaire, representing (90.3%) of the total questionnaire was the beneficiary of the health service. Using the standards statistical tests in the statistical system (SPSS 20) study found a number of important results as follows: 1) mentality image and materialistic pilot directly affect significantly, increase user satisfaction of the health service with (58,6%) from user health service opinion . 2) mentality image and materialistic pilot directly affect significantly, increase user satisfaction of the health service with (52,3%) from provider health service opinion. In conclusion, the study found a set of recommendations that have been drawn in the light of the findings of the study.